Experimental investigations of the critical values of J-integral and crack tip opening displacement (CTOD) of high-density poly-ethylene PE100 elbow. (January 2022) - Dallali, Manel; Azari, Z.; Schmitt, C.; Capelle, J.; Hadj-Taïeb, E.
Highlights: J-R and CTOD curves of HDPE have been obtained experimentally. Experimental tests were conducted in 3 directions with respect to that of extrusion. A combination of the J-integral and CTOD method is proposed to determine the JIc . Abstract: The present study aims to characterize the cracking behaviour of high-density poly-ethylene (HDPE) pipe elbow. Experimental studies were performed to determine the mechanical behaviour of HDPE and study the anisotropy of the material. Tension tests were performed on compact tension (CT) specimens to identify the toughness value, expressed by the critical value of the J-integral JIc . These tests were carried out on specimens cut from a PE100 plate with a different orientation angle with respect to the extrusion direction. The testing results have shown that HDPE can be considered as an isotropic material. The methods used to calculate the JIc value resulted in different value. Due to these uncertainties, a study of a failure criteria using crack tip opening displacement (CTOD) was proposed and conducted. The combination of the J-integral and "CTOD" method gave the possibility to determine for the critical value of the J-integral as a value of the fracture toughness of the HDPE. The obtained results suggest that the value of 8.4 kJ/m 2 can be considered as the JIc fracture toughness required to initiate the crack for the HDPE.